(untitled) (Proceedings of the International Conference on Public Health, 2019)
Assessment of medication adherence is an important part of pharmacological treatment of psychotic disorders. This study aims to obtain a valid and reliable instrument to assess medication adherence in psychotic patients. This is a cross-sectional study conducted in the Psychiatric Outpatient Clinic of Cipto Mangunkusumo Hospital from January to July 2017. Subjects were recruited through consecutive sampling (n = 100, aged 18-59 years old). Psychotic disorders were diagnosed using Structured Clinical Interview and Diagnosis DSM-IV. The instrument was translated, adapted to Indonesian culture, and back-translated. Content validity and test-retest reliability (n = 35 using systematic sampling) of MARS Indonesian version were evaluated. All items in the instrument are relevant to theory, as showed by content validity coefficient of 0.90. Construct validity test showed that the items represent theoretical as well as conceptual construction of medication adherence. Internal consistency reliability was good, with Cronbach’s alpha of 0.80 and 0.798 in the test-retest evaluation. This study produced a valid and reliable MARS Indonesian version. Currently there is no other instrument assessing medication adherence in psychotic patients in Indonesia.